Correspondência epistolar remetida por eminentes pré-historiadores espanhóis ou que trabalharam essencialmente em Espanha a José Leite de Vasconcelos (1853-1941) - Cardoso, João Luís (Estudos Arqueológicos de Oeiras, 2017)
In this article we publish and comment the correspondence sent to José Leite de Vasconcelos by twelve eminent Spanish archaeologists. Two exceptions (Georg Leisner and George Bonsor) are justified since they developed his main archaeological research in the Iberian Peninsula. The correspondence shows the high scientific and personal appreciation given to his Portuguese colleague, due not only by his scientific merit, but also by the resources he mobilized for international collaboration, with the projection of his own work, namely the journal O Arqueólogo Português and the Museu Etnológico Português, of which he was the first Director. The correspondence provides a reliable picture of the archaeological research then carried out in Spain, with interesting information about excavations then under way, with relevant information about institutions and publications, and shows the great interest of the Spanish archaeologists for reliable and up-to-date information on Portuguese Archeology.